2013
DOI: 10.13067/jkiecs.2013.8.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Functions for Mobile Robot Navigation

Abstract: This paper describes implementation of functions for mobile robot localization, which is one of the vital technologies for autonomous navigation of a mobile robot. There are several function libraries for mobile robot navigation. Some of them have limited applicability for practical use since they can be used only for simulation. Our research focuses on development of functions which can be used for localization of indoor robots. The functions implement deadreckoning and motion model of mobile robots, measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…14 Another study revealed that patients in their 60s have an average of three chronic diseases, and those in their 70s have an average of 3.5 chronic diseases. 45 Consequently, it is expected that the numbers of chronic diseases will continue to increase in seniors, and preventative measures are required. In particular, it is necessary to establish a long-term preventive strategy starting in young adulthood to address the long period to associated with the onset of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study revealed that patients in their 60s have an average of three chronic diseases, and those in their 70s have an average of 3.5 chronic diseases. 45 Consequently, it is expected that the numbers of chronic diseases will continue to increase in seniors, and preventative measures are required. In particular, it is necessary to establish a long-term preventive strategy starting in young adulthood to address the long period to associated with the onset of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%